2002
DOI: 10.1002/ffj.1149
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the essential oil of Cotinus coggygria Scop. from Turkey

Abstract: The oil from leaves of Cotinus coggygria Scop. (Anacardiaceae) obtained by hydrodistillation was analysed by GC-MS. Forty-two components were characterized, representing 99.6% of the total components detected. The major constituents were identified as limonene (48.5%), (Z )-ˇ-ocimene (27.9%) and (E )-ˇ-ocimene (9.7%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 5 publications
0
21
0
1
Order By: Relevance
“…Cotinus coggygria contains an essential oil which mainly consists of monoterpenes (Demirci et al ., ; Tzakou et al ., ; Novaković et al ., ), a high amount of hydrolysable tannins, gallic acid, methyl gallate, pentagalloyl glucose (Westenburg et al ., ) and flavonoids, glycosides of myricetin, quercetin and kaempferol (Buziashvili et al ., ). Three aurones (disulfuretin, sulfuretin and sulfurein) possessing antioxidant activity (DPPH radical scavenging activity) were isolated from C. coggygria (Westenburg et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Cotinus coggygria contains an essential oil which mainly consists of monoterpenes (Demirci et al ., ; Tzakou et al ., ; Novaković et al ., ), a high amount of hydrolysable tannins, gallic acid, methyl gallate, pentagalloyl glucose (Westenburg et al ., ) and flavonoids, glycosides of myricetin, quercetin and kaempferol (Buziashvili et al ., ). Three aurones (disulfuretin, sulfuretin and sulfurein) possessing antioxidant activity (DPPH radical scavenging activity) were isolated from C. coggygria (Westenburg et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…A methanol extract of the leaves and flowers exhibited antioxidant and cytotoxic activities (Šavikin et al ., ). The antimicrobial activity of the essential oil of C. coggygria from Turkey was not significant (Demirci et al ., ), while the essential oil found in the leaves of plants growing in Serbia inhibited the growth of Gram‐positive bacteria and fungi (Novaković et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In Bulgaria it occurs up to about 800 m asl. The plant is widely applied in the folk medicine of many countries due to its antimicrobial, anti-infl ammatory, antihaemorragic [6] and antipyretic properties [11]. The usage of Eurasian smoke tree is predominantly external and though some authors consider it poisonous [26], it has also been applied orally for treatment of throat infl ammations, paradontosis, gastric and duodenal ulcer, diarrhea [12], diabetes [14] and others.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies about phytochemical investigation of C. coggygria, it is seen that gallic tannins, flavonoids, anthocyanins and terpenes in essential oil are chemical constituents of C. coggygria (Westernburg et al 2000;Demirci et al 2003;Kültür & Bitiş 2007). It was found that C. coggygria extract has high total antioxidant activity and free radical scavenging activity, which is attributed to its high amount of total phenols and flavonoid content (Nićiforović et al 2010).…”
mentioning
confidence: 95%